Nonlinear three-dimensional finite elements for composite concrete beams - Kohnehpooshi, Omid (2012)
The use of reinforced concrete (RC) for major structural systems has increased in the recent years. Many structures such as bridges, nuclear containment systems and high rise buildings require sophisticated analysis and design procedures. RC girders for bridges have been widely used in the construction of many interstate systems and can be found in the bridge inventory of most transportation agencies. Numerical modelling of RC slab-girder bridges is used for realistic analysis of bridge superstructure. However, in the analysis of composite structures, interface structural modelling of various-type elements such as beam, truss, plate, membrane and solid element should be taken into account in order to achieve accuracy. This can be carried out by introducing suitable interface elements and taking interface translation and rotational degrees of freedom into consideration. The development and application of the interface element to model the interface behaviour between concrete and FRP are still very limited. Some of the available literature reviewed has shown that shell element has been extensively used to model FRP materials. However, little information is available regarding the use of plate bending element for FRP materials, and hence, there is a need to formulate an interface element which is compatible with the bending characteristics of this material. Therefore in this study, new interface elements have been developed,while modified constitutive law have been applied and new computational algorithm is utilised. The new elements are the Truss-link element to model the interaction between concrete and reinforcement bars, the interface element between two plate bending elements and the interface element to represent the interfacial behaviour between FRP, steel and concrete. With the tremendous advancement in the computer technologies, three dimensional (3D) finite element (FE) models have been used to study the behaviour of reinforced concrete beams, with and without externally bonded fibre reinforced polymer (FRP) plates. The current investigation focused on the development of effective and suitable modelling of reinforced concrete beam with and without strengthening. The modelling includes physical and constitutive models, from which the nonlinear finite-element (FE) codes were developed with pre- and post-processing. The programme was written using FORTRAN language and it works under FORTRAN-95 Power Station. The accuracy and efficiency of the finite element programmes were achieved by analyzing several examples from the literature. For instance, the finite element discretisation of different numerical examples was used for the verification purposes and also computational efficiency. The application of the 3D FE code was further enhanced by carrying out the numerical analysis of the RC beams post-tensioned in the critical shear region, analysis of single lap joint, three dimensional finite element analysis of FRP strengthened RC beams, as well as analysis of the anchored reinforcing bars under monotonic pull-out load and the 3D nonlinear finite element analysis of girder bridge. During these applications, the distributions of deflection, slip of bars inside the concrete, normal and shear stresses of concrete, axial and shear stresses in the FRP plates, normal and shear stresses of single lap joint and slip of bars due to pull-out test were monitored. Acceptable distributions of slip, deflection, shear and axial stresses in the FRP plate have also been found. These results show that the new elements, which include Truss-linkage element and interface elements, are effective and appropriate to be used for structural component modelling.